Development and initial evaluation of a rigid rhinoscopy model as a pedagogic tool in veterinary medicine - Myerow, Bethany Sabatino; Pritchard, Jessica C.; Kalscheur, Kathryn; Marks, Steve; Royal, Kenneth; Thoreson, Nicholas; Pollard, Noah; Hawkins, Eleanor C. (Frontiers in Veterinary Science, 2024)
No model exists to train the handling skills required for successful performance of rigid rhinoscopy in veterinary patients. The complex anatomy of the nasal cavity, the limited space between turbinates, and the propensity of the mucosa to bleed with slight trauma make thorough examination of a nasal cavity difficult. The goal of this study was development and initial testing of a low fidelity canine rigid rhinoscopy training model for veterinary novices. A model comprising three tubes of various lumen diameters that were connected to a conduction system was created. Each tube contained three colored stars and a number that were to be described by trainees. The model both counted contacts and audibly beeped if pressure was applied by the rhinoscope to the sides of the tube. Board-certified veterinary internists (experts) and veterinary students (novices) performed two timed simulation exercises during a single session. Participants completed a questionnaire before and after the simulations to assess model utility. There were no statistically significant differences in contacts or time to completion between novices and experts. Novices provided feedback that the model improved their ability to control the rhinoscope, helped them learn to perform rigid rhinoscopy, was enjoyable, and was appropriately challenging. Expert feedback included that the model was a potentially useful pedagogic tool for training rigid rhinoscopy, including hand control and indirect hand-eye coordination, and was appropriately challenging. We conclude that this rhinoscopy model has potential to be an effective teaching tool for novice rhinoscopists. With minor modifications, the model could provide additional challenges.